Electro-discharge machining of SUS 304 stainless steel with TaC powder-mixed dielectric - Mohd. Zain, Zakaria; Ndaliman, Mohammed Baba; Khan, Ahsan Ali; Mohammad , Yeakub Ali (2012)
Powder-mixed dielectric fluid is one of the innovations of electro-discharge machining (EDM) which seeks to improve the process outputs by addition of powders to the dielectric during machining. In the present study, the influence of TaC powder in kerosene dielectric fluid on EDM process outputs was investigated. Experiments were conducted with the outputs as material removal rate (MRR), surface roughness (Ra) and micro-hardness. During the EDM, the discharge current was varied between 2.5 and 6.5 A, while powder concentration ranges between 5.0 and 15.0 g/l. Results indicate that the highest MRR of 0.38 g/min was obtained with TaC concentration of 15 g/l at the current of 6.5 A. TaC powder addition does not affect both the MRR and Ra at lower current. However, the level of micro-hardness attained was influenced by TaC powder concentration in dielectric fluid, the highest being 1,040 Hv with 5.0 g/l at the current of 2.5 A.